Songgolangit FM Radio Convergence Strategy in The Middle of The Broadcasting Industry Competition in Ponorogo - Devi, Imasnyti Ciptanti (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstract: Radio Songgolangit FM Ponorogo which is considered to have implemented the practice of media convergence. In the current era of media convergence, radio, which is considered a traditional media, must survive in the midst of increasingly fierce competition in the broadcasting industry to expand its audience and receive advertisements. This research is a descriptive study with a qualitative approach to describe the convergence strategy of Songgolangit FM radio in the midst of the competition in the broadcasting industry in Ponorogo. The data collection technique was carried out by using observation, interviews, and documentation owned by Radio Songgolangit FM then describing the subject under study. Based on the results of the analysis, it can be concluded that the convergence strategy of Songgolangit FM radio uses 3M, namely multimedia, multichannel, and multiplatform. Where information is presented in various formats ranging from photos, video, text, and audio. Meanwhile, all information is not only conveyed via broadcast radio but uploaded via social media and can be accessed through the respective audience devices. The implications of the convergence practice of Songgolangit radio are divided into social, cultural and economic implications. So, with the impact, Songgolangit FM radio can take advantage of the convergence era so that it can survive in the midst of intense competition in the broadcasting industry, especially in Ponorogo.